Present Characteristics of Northwestern Patagonia (Argentina) - Scarpati, Olga E.; Botana, Maria I.; Capriolo, Alberto D.; Pohl Schnake, Veronica; Puga, Yamile; Salaverry, Edgardo (Water (Basel), 2011)
Changes experienced in temperature, precipitation, demography and land coverage are the main themes studied in northwestern Patagonia, Argentina, which includes part of Neuquén, Río Negro and Chubut provinces. The precipitation shows important interannual variability and decreases during the warm semester. The mean minimum temperature in January in Neuquén city increased with statistical significance. Forests and steppe are the more important ecosystems of the area and the native forests of Nothofagus sp. are located mainly in protected areas like National or Provincial Parks. Twenty-eight percent of the Andean—patagonic forests are in the Río Negro province, while Neuquén province has 9% and Chubut province has 26%. The censuses of 1991 and 2001 showed that Los Lagos, Lacar, Picún Leufú and Cushamen are the counties with increasing population.